Advocating for the Inclusion of Fine Arts in the Healthcare Education Curricula: The Lived Experience of an Art-Loving Healthcare Educator - Ko, Cindy (Journal of Practical Nurse Education and Practice, 2025)
The incorporation of fine arts into healthcare education curricula could enrich students' overall learning experiences, enhance cognitive and emotional development, and prepare them for the diverse, dynamic, and stressful workplace. In this paper, I will offer my lived experience of using the arts in to engage nursing and health sciences students’ participation. The paper begins with a brief definition and scope of the arts to anchor the discussion and a variegated collection of literature scan. I will present the various cognitive and professional benefits of integrating the arts into healthcare curricula. I will append photos of several past and contemporary international artists’ works, including personal communications that would reinforce my assertion. In addition, I will include anecdotes from students and others who shared their insights on the integration of the arts in learning. I will also discuss practice implications and recommendations for including the arts in curriculum development.